Analisis Kelayakan Pompa Elektrik Pemadam Kebakaran Klinik Mata PT X - Fasli; Rudi Hariyanto; Fransiskus Asisi Widiharsa; Darto; Pradhana Kurniawan (TRANSMISI, 2025)
In a pumping system, one important parameter that needs to be analyzed is the hydraulic power needed to move the fluid. This hydraulic power reflects how much energy is needed to move the fluid through the piping system, and this is highly dependent on factors such as flow rate, head, and the characteristics of the pump itself. The purpose of this Pkn is to determine the hydraulic power of the pump. In pumping, it is necessary to pay attention to several factors so that the pump can work optimally, such as the height of the water to be sucked and the height of the building to be distributed and the design of the pipes as water channels. The method used to determine the hydraulic power of the pump is through data collection. From the results of data processing, we can find out the different flow rate values ​​based on the discharge and pipe diameter, flow losses obtained at pipe joints such as major losses and minor losses, the power required to drive the pump is 55 KW and the hydraulic power is 45.53840 KW, and the pump efficiency is 82.79%.